1967
DOI: 10.1002/jsfa.2740180410
|View full text |Cite
|
Sign up to set email alerts
|

Studies on potassium nutrition of plants. I.—Effects of potassium concentration on growth and mineral composition of vegetable seedlings in sand culture

Abstract: found recently that 3-t butyl and 2,4-di-t-butyl cyclopentadienones are more stable as monomers.The effect of potassium concentration in the nutrient medium on growth and mineral composition (N, K, P, Ca, Mg, Na) of red beet, cabbage, lettuce and Italian ryegrass in sand culture was investigated. It was shown that the results and those of some earlier workers can be interpreted as a simple linear relationship where y is plant weight or leaf !potassium content, x is potas-1 by means of the equation: -= a + -Y x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Ca content of plants (4,9,11,13,16,17,22). Lazaroff and Pitman (13) found the depressive effect of monovalent cations on Ca content to be confined to the tops of barley plants and to occur only at high concentrations of monovalent cations (5000-60,000 /AI Na + K).…”
Section: Inereasinig Coneentrations Of K Generally Depressmentioning
confidence: 99%
“…Ca content of plants (4,9,11,13,16,17,22). Lazaroff and Pitman (13) found the depressive effect of monovalent cations on Ca content to be confined to the tops of barley plants and to occur only at high concentrations of monovalent cations (5000-60,000 /AI Na + K).…”
Section: Inereasinig Coneentrations Of K Generally Depressmentioning
confidence: 99%
“…Potassium and sodium values were characteristic of these components of cabbage seedlings grown at the stated potassium concentrations in the medium. 8 The effect of potassium nutrition on the ionic balance of potassium and sodium and of potassium and calcium plus magnesium has been reported and discussed in earlier papers in this ~e r i e s .~J~ 'Protein' contents (total N x 6.25) varied slightly from K O to K5.0 but the variation was small compared with that of the ,corresponding values of K and Na and it was concluded that this component showed no definite trend with changes of leaf potassium content. A curve relating sugar content with potassium concentration in the growth medium (not reproduced here) rose steeply and almost linearly from KO.05 to K0.25 and then flattened out at the highest K + concentrations.…”
Section: Results and Discussion Effect Of Potassium Nutrition On Leafmentioning
confidence: 99%
“…This was due to the higher K concentration in the soil and oil palm leaf in the EFB treatment. According to Lazaroff and Pitman (1966) and Freeman (1967), high K concentration reduces Ca uptake by plants. In this study, the effect of EFB on increasing soil Ca concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%